Pengaruh Social Media Marketing, Word of Mouth, Label Halal dan Harga Terhadap Keputusan Pembelian Produk Kosmetik Brand Haveloek - Salsabila Azaria; Hendra Achmadi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study is to determine whether word of mouth, online cutsomer ratings, social media marketing, price and halal label have a positive influence on purchasing decision for cosmetic product of the Haveloek brand. This study is driven by stagnant sales performanca of Haveloek, which shows a significant gap compare to other local brand. The sample consist of Haveloek consumers in JABODETABEK area with total of XX respondents. The sampling technique used is puporsive sampling and data analysis was carried out using SMART PLS application with the PLS-SEM method. The result of this study are expected to provide insights for Haveloek in designing more effective marketing strategies to improve its competitiveness in the Indonesia cosmetic industry. This study demonstrates a positive influence of social media marketing, word of mouth, price, and halal label on the purchase decision of Haveloek cosmetic products.